Predictors of Agitation in the Adult Critically Ill - Burk, Ruth S. (Am J Crit Care, 2014)
BACKGROUND: Agitation in critically ill adults is a frequent complication of hospitalization resulting in multiple adverse outcomes. Potential causes of agitation in critically ill patients are numerous; however, data about factors that predict agitation are limited. OBJECTIVES: The purpose of this study is to identify predictors of agitation by investigating demographic and clinical characteristics of critically ill patients. METHODS: A medical record review was performed identifying agitation using the Richmond Agitation-Sedation Scale or the use of an “agitation” keyword. A total of 200 patients were studied from a medical and surgical ICU. Two models were examined: 1) on admission and 2) 24 hours prior to the first agitation event. Data pertaining to baseline demographics and preadmission risk factors as well as clinical data were collected and evaluated by logistic multivariable regression to determine predictors of agitation. RESULTS: Predictors of agitation on admission to the ICU were: past medical history of illicit substance use, height, both the Sequential Organ Failure Assessment (SOFA) respiratory and central nervous system subscores, and use of restraints. Predictors of agitation identified from data gathered within 24 hours prior to agitation were: past medical history of psychiatric diagnosis, height, SOFA score, P/F<200mmHg, serum pH, percent of hours using restraints, percent of hours using mechanical ventilation, pain, and presence of genitourinary catheters. CONCLUSIONS: In this study predictors of agitation on admission and within 24 hours prior to agitation onset were primarily clinical variables. This allows considerable opportunity for intervention to ameliorate or prevent agitation.